Hubungan antara Tingkat Depresi dengan Kualitas Hidup Pasien Chronic Kidney Disease yang Menjalani Hemodialisis di RSD dr. Soebandi Jember (Correlation between Level of Depression and Quality of Life of Chronic Kidney Disease Patients During Hemodialysis - Nindhya Kharisma Putri; Justina Evy Tyaswati; Ali Santosa (Pustaka Kesehatan, 2016)
Chronic Kidney Disease (CKD) is secondary disease with irreversible process of progressive reduction in kidney function, one of the therapy is hemodialysis which can cause psychological disorders. The most frequently occured is depression that can reduce quality of life of CKD patients. The aim of this research was to analyze the correlation between level of depression and quality of life of CKD patients during hemodialysis therapy. This research used Cross Sectional Design with 30 respondents. The data were collected from hemodialysis policlynic at dr. Soebandi hospital Jember. The level of depression was measured using HDRS questionnair, and quality of life was measured using WHOQOLBREF questionnair. The result showed that 50% respondents had mild depression (23,3% respondents had good quality of life and 26,7% respondents had bad quality of life), 23,3% respondents were moderate depression (3,3% respondents had good quality of life and 20% respondents had bad quality of life), while 26,7% respondents were severe depression who had bad quality of life. The Spearman correlation test showed that the significance (p) of this test was 0.010 with -0.464 correlation coefficient (r). It can be concluded that there were correlation between level of depression and quality of life of CKD patients during hemodialysis therapy at dr. Soebandi regional hospital Jember. Keywords: Chronic Kidney Disease (CKD), depression, quality of life, hemodialysis.